Rise and fall of an anti-MUC1 specific antibody - Thie, Holger; Toleikis, Lars; Li, Jiandong; Wasielewski, Reinhard von; Bastert, Gunther; Schirrmann, Thomas; Esteves, Isabel Tourais; Behrens, Christian K.; Fournes, Bénédict; Fournier, Nathalie; Romeuf, Christophe de; Hust, Michael; et al. (PLOS ONE, 2011)
Background So far, human antibodies with good affinity and specificity for MUC1, a transmembrane protein overexpressed on breast cancers and ovarian carcinomas, and thus a promising target for therapy, were very difficult to generate. Results A human scFv antibody was isolated from an immune library derived from breast cancer patients immunised with MUC1. The anti-MUC1 scFv reacted with tumour cells in more than 80% of 228 tissue sections of mamma carcinoma samples, while showing very low reactivity with a large panel of non-tumour tissues. By mutagenesis and phage display, affinity of scFvs was increased up to 500fold to 5,7×10−10 M. Half-life in serum was improved from below 1 day to more than 4 weeks and was correlated with the dimerisation tendency of the individual scFvs. The scFv bound to T47D and MCF-7 mammalian cancer cell lines were recloned into the scFv-Fc and IgG format resulting in decrease of affinity of one binder. The IgG variants with the highest affinity were tested in mouse xenograft models using MCF-7 and OVCAR tumour cells. However, the experiments showed no significant decrease in tumour growth or increase in the survival rates. To study the reasons for the failure of the xenograft experiments, ADCC was analysed in vitro using MCF-7 and OVCAR3 target cells, revealing a low ADCC, possibly due to internalisation, as detected for MCF-7 cells. Conclusions Antibody phage display starting with immune libraries and followed by affinity maturation is a powerful strategy to generate high affinity human antibodies to difficult targets, in this case shown by the creation of a highly specific antibody with subnanomolar affinity to a very small epitope consisting of four amino acids. Despite these “best in class” binding parameters, the therapeutic success of this antibody was prevented by the target biology.
Gesehen am 27.10.2022